FET-PET assessed recurrence pattern after radio-chemotherapy in newly diagnosed patients with glioblastoma is influenced by MGMT methylation status - Niyazi, Maximilian; Schnell, Oliver; Suchorska, Bogdana; Schwarz, Silke Birgit; Ganswindt, Ute; Geisler, Julia; Bartenstein, Peter; Kreth, Friedrich Wilhelm; Tonn, Jörg Christian; Eigenbrod, Sabina; Belka, Claus; La Fougère, Christian (Radiotherapy and Oncology, 2012)
Background and purpose: The aim of the present study was to evaluate factors predicting the recurrence pattern determined by [18F]FET-PET imaging in patients with newly diagnosed glioblastoma after combined radio-chemotherapy treated according to the EORTC/NCIC trial. Material and methods: Seventy-nine patients with newly diagnosed GBM treated with radiotherapy plus temozolomide (75 mg/m2/d) followed by adjuvant cyclic (5/28 days) temozolomide (150-200 mg/m2) were retrospectively analysed. Recurrence patterns were assessed by means of positron-emission- tomography with [18F]FET and additional MRI; in 54 patients MGMT methylation status was evaluated. Results: Whilst 49.4% of the patients had an in-field recurrence, 12.6% an ex-field recurrence and 3.8% a recurrence at the field margin, 34.2% of the patients did not relapse during follow-up (median 595 days). Considering all patients included in this study, 41.5% (12/29) of the MGMT methylated population had no relapse, 37.9% (11/29) had an in-field-recurrence and 20.7% (6/29) an ex-field/marginal recurrence, whilst 28.0% (7/25) of the MGMT unmethylated population had no relapse, 64.0% (16/25) had an in-field-recurrence and 8.0% (2/25) an ex-field/marginal recurrence (p = 0.15). Conclusions: After the administration of temozolomide concomitant with and adjuvant to radiotherapy in patients with glioblastoma, the pattern determined by [18F]FET-PET seems to be associated with MGMT methylation status. © 2011 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-09-13
Keywords: FET-PET; Glioblastoma; MGMT; Radio-chemotherapy; Recurrence pattern